Analisis prospektif pembelajaran konsep kesebangunan kelas VII SMP - Fuadiah, Nyiayu Fahriza; Fadhilah, Fadhilah; Lestaria Ningsih, Yunika (IKIP Siliwangi, 2025)
This study aims to identify learning obstacles and develop a Hypothetical Learning Trajectory (HLT) for teaching the concept of similarity in Grade VII. The research is part of Didactical Design Research at the prospective analysis stage. Data were collected through textbook review, analysis of instructional materials, curriculum documents, diagnostic tests, and interviews with teachers and students. Analysis techniques include qualitative analysis, descriptive statistics, and data triangulation. Findings reveal types of learning obstacles: (1) ontogenetic, low conceptual readiness; (2) epistemological, inability to relate ratios to similarity conditions, compare corresponding sides, and make sketches; and (3) didactic, materials that lack explicit explanation of similarity conditions, offer few contextual activities, and focus on procedures. Based on these findings, the HLT includes three goals: informal recognition of similarity, identifying similar triangles based on conditions, and solving contextual problems through exploratory activities, group discussion, and real-life contexts. The study implies that systematic identification of learning obstacles is essential for designing more adaptive and meaningful instructional interventions.